Understanding the Sorghum–Colletotrichum sublineola Interactions for Enhanced Host Resistance - Abreha, Kibrom B.; Ortiz, Rodomiro; Carlsson, Anders S.; Geleta, Mulatu (Frontiers in Plant Science, 2021)
Improving sorghum resistance is a sustainable method to reduce yield losses due to anthracnose, a devastating disease caused by Colletotrichum sublineola. Elucidating the molecular mechanisms of sorghum–C. sublineola interactions would help identify biomarkers for rapid and efficient identification of novel sources for host-plant resistance improvement, understanding the pathogen virulence, and facilitating resistance breeding. Despite concerted efforts to identify resistance sources, the knowledge about sorghum–anthracnose interactions remains scanty. Hence, in this review, we presented an overview of the current knowledge on the mechanisms of sorghum-C. sublineola molecular interactions, sources of resistance for sorghum breeding, quantitative trait loci (QTL) and major (R-) resistance gene sequences as well as defense-related genes associated with anthracnose resistance. We summarized current knowledge about C. sublineola populations and its virulence. Illustration of the sorghum-C. sublineola interaction model based on the current knowledge is also provided. We highlighted the importance of genomic resources of both organisms for integrated omics research to unravel the key molecular components underpinning compatible and incompatible sorghum–anthracnose interactions. Furthermore, sorghum-breeding strategy employing rapid sorghum germplasm screening, systems biology, and molecular tools is presented.